Headache and hypothalamic syndrome - M. G. Zhestikova; I. R. Schmidt; N. P. Shakhvorost (Бюллетень сибирской медицины)
We have carried out a comparative analysis of peculiarities of headache at patients with adenoma of hypophis and hypotolamic syndrome of complicated genesis. 611 sick people were checked up (472 females and 139 males): 311 with adenomas of hypophis and 300 with hypotolamic syndrome. Methods of investigation: for appreciation of headache we analyzed qualitative and spatial — temporary descriptions and provokating factors. Double-sided headache at parients with adenomas of hypophis was in 2,5 more often than at patients with hypotolamic syndrome. Correlation of frequency of left- and right-side localization was also different: 1,6 : 1 — at sick people with hypotolamic syndrome and 1 : 1,1 — with adenomas of hypophis.